Hubungan Tingkat Pendapatan Terhadap Peningkatan Kesejahteraan Rumah Tangga Pengusaha Tahu Tempe - Kamaruddin (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
This study aims to determine the relationship between income levels and the level of welfare of tofu and tempeh entrepreneurs. The research used a quantitative descriptive research approach. The population in this study was 28 tofu and tempeh entrepreneurs. And the sample used population research because it was less than 100 people. The data collection techniques used were interviews and observations. With the type of data, namely quantitative data, while the data sources used were primary data. Data analysis techniques were income analysis, simple regression analysis, and t-test as a hypothesis test. Based on the results of the income analysis, it shows the results of the activities of tofu and tempeh entrepreneurs whose average amount is IDR 3,866,071 per month and is large enough to help and improve their family's economy. This can be seen from the results of the hypothesis test with the t-test which shows t count = 3.830> t table = 1.813 so that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted with the direction of regression Y = 3.7 + 1.2X. This shows that the independent variable (income level) has a positive and significant effect on the dependent variable (the level of welfare of tofu and tempeh entrepreneurs' households). For further research, it is expected to take more samples and use other variables besides the variables used by the current researcher, so that it can attract the interest of the community to process this tofu and tempeh even more.